Differential analysis of splenic immune indicators, transcriptomic profiles, and metabolomic features in pigs under liquid–solid feeding conditions - Liu, Yangguang; Zhu, Cuiyun; Zhang, Huibin; Xie, Fan; Ye, Haibo; Zhao, Shiming; Wang, Qianqian; Zheng, Xianrui; Yin, Zongjun; Zhang, Xiaodong (Frontiers in Veterinary Science, 2026)
IntroductionFermented liquid feed (FLF) has been shown to improve feed efficiency and growth performance of pigs, however, its effects on porcine immune function remain poorly understood.MethodsIn this study, transcriptomic, metabolomic, and ELISA-based approaches were employed to systematically evaluate the effects of fermented liquid feed on immune factor levels, splenic metabolic profiles, and gene expression in pigs. A total of 64 commercial pigs were randomly assigned to two groups, fed a basal diet group (CON) and a fermented liquid diet group (LFF), for a feeding period of 60 days.ResultsThe results showed that, compared with the CON group, the LFF group exhibited significantly higher serum concentrations of interleukin-6(IL-6, 767.88 ± 12.43 pg/ml), tumor necrosis factor-α(TNF-α 678.32 ± 15.37 pg/ml), complement C3(145.92±3.69 μg/ml), immunoglobulin A(IgA, 485.15 ± 9.13 μg/ml), and interferon-γ(IFN-γ 1966.76 ± 72.22 pg/ml). Meanwhile, transcriptome sequencing revealed that the expression levels of immune-related genes CXCL2, CXCL8, and SLA-5 were significantly upregulated in the LFF group. Further KEGG pathway analysis demonstrated a more pronounced enrichment of the chemokine signaling pathway and IL-17 signaling pathway in this group. The metabolomic analysis revealed that fermented liquid feed altered the metabolic profile of the spleen, primarily affecting the biosynthesis of unsaturated fatty acids and linoleic acid metabolism. Integrated analysis indicated that fermented liquid feed reprogrammed metabolic patterns by modulating the expression of immune-related genes.DiscussionIn conclusion, our findings indicate that fermented liquid feed significantly enhances immune function in pigs, providing a theoretical basis for its scientific application and promotion in healthy farming of pigs.